Ethnomethodology Study in Cultural Identification As A Potential Social Resource to be Developed in Ranu Pani Village - Ibrahim, Ananda Ravelio Nur; Wagistina, Satti; Deffinika, Ifan (Lembaga penelitian dan pengabdian kepada Masyarakat, 2022)
The Bromo Tengger Semeru National Park Conservation Area is a tourist attraction because of its natural and cultural wealth. Natural tourism has flourished in Bromo Tengger Semeru National Park Conservation, but the cultural potential has not developed optimally. Ranu Pani Village is a village within the Bromo Tengger Semeru National Park Conservation region of cultural diversity and uniqueness, populated by the Tengger society. The study aims to identify the Ranu Pani Village people's culture and design tourism activities from such identification. The method used in this study is the ethnomethodology of Spradley analysis. Ethnomethodology is used to dig up information about people's culture through a direct approach to society. The retrieval of data relating to cultural forms and tourism in the village of Ranu Pani with in-depth interviews, observation, and documentation. Studies have shown that Dukun Pandita is essential role in preserving the cultural community. Local cultures, such as the Karo custom and music ceremonies, can be used as regular tourist attractions by integrating the Tengger calendar system with E-information so that the tourists can know the time for the ceremony. There is also an art of Sodoran dance and folklore that can be collaborated with traditional music studios of cultural houses and Rondo Kuning temple studio performances of the music in previously unused amphitheaters.